The processes taking place in the USA and Republic of Georgia (October-March, 1990-1991) - Shvelidze, Erekle (HISTORY, ARCHAEOLOGY, ETHNOLOGY; No I (2018), 2018)
The represented work aims to determine the character of attitude of the USA Government and official circles towards the authorities of newly declared Republic of Georgia. The countries of the Western World which recognized the USSR, avoided settling the relations with newly declared former Soviet Republics and especially Georgia among others. Despite this fact the leader state of the West – the USA tried to show their interest in indirect ways towards the national and democratic processes taking place in Georgia. The USA Government greeted the multi-partial elections which brought the communist era to the end. The so called “parallel tactics” announced by the USA was an important initiative n that period of time. It was an important fact that on the day when Referendum was taking place in Georgia the results of which showed that great majority of the population voted for the Independence, ex-president Richard Nixon visited Tbilisi. In its turn, the new government of Georgia was trying to express their support to the USA and other democratic countries of the world in their actions against Iraq.